Users ’ awareness and satisfaction with the Biodiversity information in Tanga, Dar es Salaam, Morogoro and Coast regions. - Mungwabi, Hosea N; Kilemile, Joram S. (University of Dar es Salaam Library Journal, 2017)
This article examines the users ' awareness and satisfaction with biodiversity information that was being provided by their respective information systems. The study was conducted among biodiversity databases user communities in Tanga, Morogoro, Dar es Salaam and Coast regions of Tanzania. Mixed research design was used in which techniques such as questionnaires, observation, interviews and focus groups ' discussions were employed to collect both qualitative and quantitative data. The key findings indicate that the majority of the respondents were not aware of the existence of biodiversity information in their institutions. The respondents who seemed to be aware of its existence opined that biodiversity information which was being dispensed by their information systems was relevant but not updated and adequate for planning and decision-making. The article incorporates some recommendations on how the situation may be improved to enhance access and use of the biodiversity information in Tanzania.